Germination of artocarpus integer and durio zibethinus Murr. Seeds following accelerated aging - Jekim, Jirap. (Universiti Malaysia Sarawak (UNIMAS), 2004)
A study was conducted to evaluate the effects of short period of accelerated aging and storage on the germination of Artoearpus integer and Durio zibethinus Murr seeds. The seeds were place in dessicators to aged for three days at 40-42°C and 100% relative humidity. After accelerated aging treatment seeds were put in air-tight bottles and stored in a dessicator in a oven (40-42°C) for 2 weeks. Accelerated aging caused a decreased in germination of seeds for A. integer (decrease from 88% to 0% in 5 days) and D. zibethinus Murr (decreased from 96% to 0% in 6 days). Different environments of varying temperatures of storing seeds gave different results in percentage of seed germination. Germination percentage of aged seeds decreased with increase in the period of aging and storage.